2008
DOI: 10.1152/ajprenal.00488.2007
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic paraventricular nucleus is critical for renal vasoconstriction elicited by elevations in body temperature

Abstract: Redistribution of blood from the viscera to the peripheral vasculature is the major cardiovascular response designed to restore thermoregulatory homeostasis after an elevation in body core temperature. In this study, we investigated the role of the hypothalamic paraventricular nucleus (PVN) in the reflex decrease in renal blood flow that is induced by hyperthermia, as this brain region is known to play a key role in renal function and may contribute to the central pathways underlying thermoregulatory responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…Neurons in the PVN are activated by increases in ambient temperature, including those that influence sympathetic nerve activity (3,7,9,27), suggesting a role for the PVN in temperature regulation. The present study, together with our more recent work showing that inhibition of neuronal function within the PVN prevented the hyperthermia-induced reduction in renal and mesenteric blood flows, provides direct evidence that the PVN plays a key role in the cardiovascular thermoregulatory responses (8,10). This does not exclude other brain regions contributing to the reflex renal vasoconstriction elicited by hyperthermia.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Neurons in the PVN are activated by increases in ambient temperature, including those that influence sympathetic nerve activity (3,7,9,27), suggesting a role for the PVN in temperature regulation. The present study, together with our more recent work showing that inhibition of neuronal function within the PVN prevented the hyperthermia-induced reduction in renal and mesenteric blood flows, provides direct evidence that the PVN plays a key role in the cardiovascular thermoregulatory responses (8,10). This does not exclude other brain regions contributing to the reflex renal vasoconstriction elicited by hyperthermia.…”
Section: Discussionsupporting
confidence: 59%
“…Our hypothesis is that the PVN is the key site, since it has a dense concentration of ANG II type 1 receptors and that inhibition of the PVN prevents the reflex vasoconstriction in renal and mesenteric vasculature (1,8,10). In the present study, therefore, we investigated the effect of microinjection of the ANG II type 1 receptor antagonist, losartan, directly into the PVN on the reflex reduction in renal blood flow induced by elevating body core temperature in rats.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, we found that the PVN also plays a critical role in the reflex reduction in renal blood flow elicited by an increase in core body temperature (10). This effect was also specific to the PVN.…”
Section: Discussionmentioning
confidence: 69%
“…More recently we have provided strong evidence indicating that the PVN is essential for the reflex vasoconstriction of the renal vasculature induced by an elevation in core body temperature (10), indicating that the hypothalamic PVN is functionally important in the cardiovascular reflex responses of the renal vasculature elicited by hyperthermia. Whether the role of the PVN is confined to the renal vasculature or whether the PVN contributes to the decrease in mesenteric blood flow that also accompanies an increase in core body temperature is not known.…”
mentioning
confidence: 95%